2022
DOI: 10.1111/aej.12682
|View full text |Cite
|
Sign up to set email alerts
|

Internal morphology of distal roots of mandibular first molars revealed by computed microtomography

Abstract: To evaluate the internal morphology of 100 distal roots of mandibular first molars using micro‐CT. Teeth were scanned to characterise: Vertucci type, root length, canal shape, presence and location of accessory canals, and the number of foramina at 4 mm from the apex, presence of root isthmus and the length from the primary canal to the apical foramen. Vertucci type I was found in 57% of cases, followed by V (27%). The most common cross‐section 1 mm from the apex was oval (49%) and circular (38%). The average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…(P> 0.05). Table (1,2) These results were agreed with a study by Marceliano-Alves et al, (2022) (4) showing no significance difference between Hyflex EDM and ProTaper Next at all root canal level and both systems respecting the original anatomies during instrumentation.…”
Section: Resultssupporting
confidence: 91%
“…(P> 0.05). Table (1,2) These results were agreed with a study by Marceliano-Alves et al, (2022) (4) showing no significance difference between Hyflex EDM and ProTaper Next at all root canal level and both systems respecting the original anatomies during instrumentation.…”
Section: Resultssupporting
confidence: 91%
“…The most frequent mesial root canal configuration in the first mandibular molar is type IV (46.2%), followed by type II (16.3%). In the distal canal, type I was found in 57% of cases, followed by V (27%) 8 . Another study on distal canals found 88.6% type I and other atypical configurations 9 .…”
Section: Introductionmentioning
confidence: 95%